Plasma interferon-γ-inducible protein 10 (IP-10) levels correlate with disease severity and paradoxical reactions in extrapulmonary tuberculosis - Suárez, Isabelle; Rohr, Samuel; Stecher, Melanie; Lehmann, Clara; Winter, Sandra; Jung, Norma; Priesner, Vanessa; Berger, Melanie; Wyen, Christoph; Augustin, Max; Malin, Jakob J.; Fischer, Julia; et al. (Infection, 2021)
With 1.5 million deaths worldwide in 2018, tuberculosis (TB) remains a major global public health problem. While pulmonary TB (PTB) is the most common manifestation, the proportion of extrapulmonary TB (EPTB) is increasing in low-burden countries. EPTB is a heterogeneous disease entity posing diagnostic and management challenges due to the lack of reliable biomarkers. In this study, we prospectively evaluated clinical data and treatment response which were correlated with different biomarkers.